Related Factors of Work Stress Among Breastfeeding Working Women in Indonesia - Lubis, Siti Rahmah Hidayatullah; Susilowati, Indri Hapsari (Media Kesehatan Masyarakat Indonesia, 2023)
Work stress is a common response experienced by workers, including breastfeeding working women, due to stressors arising in the workplace. In the short term, work stress has a negative impact on the productivity and lactation activity of working women. Therefore, this study aimed to investigate the factors associated with work stress among breastfeeding working women. A cross-sectional design was used by distributing the workplace stress scale questionnaire and additional questions to breastfeeding working women. The data used were obtained from 162 respondents spread across Indonesia who were willing to fill out online questionnaires. Subsequently, the collected data were analyzed using the Logistic Regression test. The results indicated that 85 people (52.47%) felt high stress, particularly regarding the lack of opportunity to show ability and talent during work. A statistically significant relationship (p=0.034, aOR= 2.139) was also discovered between the type of family and work-related stress in breastfeeding working women. Although this problem was directly sourced from stressors at work, demographic factors such as the type of family contributed to the stress experienced by breastfeeding working women.